Evolutionary Game Analysis of Cross-Border E-Commerce Logistics Alliance Subject Considering Supply Chain Disruption Risk - Yang, Xiaochun; Jiang, Huiyuan; Chen, Wenxia (Sustainability, 2023)
Due to the quick rise in cross-border e-commerce and the expansion of global economic integration, cross-border e-commerce logistics alliances now present new opportunities and potential. Simultaneously, research on risk concerns in cross-border e-commerce in the modern era has drawn interest. This paper considers the special scenario of cross-border e-commerce supply chain disruptions, analyzes the main decision-making behaviors of key entities in the cross-border e-commerce logistics alliance under normal and risk scenarios, and based on this, constructs a tripartite evolutionary game model among cross-border e-commerce platforms, logistics service providers, and overseas merchants. The article analyzes the evolutionary stability of strategy choices for all participants, discusses the impact of various elements on the strategy choices of the three parties, and conducts a simulation analysis of the dynamic game of strategy choices for the three parties under the influence of different parameters using MATLAB 2021a software. The findings of the study demonstrate the following: (1) The reduction in the allocation coefficient for additional total costs of logistics service providers, the increase in the overall losses of the alliance due to customer complaints, and the increase in compensation rulings by the platform for supply chain risks faced by merchants will all encourage logistics service providers to actively pursue service innovation strategies and prompt overseas merchants to actively participate in alliance cooperation. However, an increase in overall risk costs and an increase in opportunity costs for merchants will raise the costs of tripartite alliance cooperation, thus hindering cross-border e-commerce logistics alliance collaboration. At the same time, when logistics service providers receive punishment from the platform and face potentially increased losses due to complaints, this will not only enhance the platform’s control over logistics service providers but also reduce the enthusiasm of logistics service providers to pursue service innovation strategies. (2) As the main body of the alliance, cross-border e-commerce platforms should coordinate the participants, constrain the behaviors of the participating entities within the alliance through setting reasonable reward and punishment mechanisms, and ensure the comprehensive benefits of the cross-border e-commerce logistics alliance through the combined effect of different exogenous variables. Finally, through the analysis, verification, and explanation of the established model and methods, the effectiveness and applicability of the model and methods are confirmed, providing certain strategic support and a development reference for actively establishing cross-border e-commerce logistics alliances to promote cross-border e-commerce trade.